UPAYA PBB DALAM MENGHENTIKAN PROLIFERASI NUKLIR KOREA UTARA TAHUN 2009-2013 - Heru Winata; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This studywillanalyzeabout thenuclear testby North KoreaandUNeffortstohaltthe proliferation ofnuclearweaponsNorth Koreain 2009-2013. OnFebruary 12, 2013, NorthKoreanmediaannouncedthatthe country haslaunched anunderground nuclear testisa test ofthreein a span ofsevenyears. NorthKoreahas conductedthreenuclearweapons test, namelyin 2006, 2009 and2013.UNfinallyimposed sanctions onNorthKoreaandpassed Resolution2094,whichcondemnedtheactionand imposeda series ofsanctionstodetereffortsto furtherdevelopits nuclearcapabilitiesThis study used the international organization theory. The author also defines the scope of this study which is from 2009-2013.Keywords: Nuclear,United Nations, Resolution, Poliferation.